2009
DOI: 10.2337/db09-0091
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus Infection, CXC Chemokine Ligand 10 (CXCL10), and CXCR3 Circuit

Abstract: OBJECTIVEFulminant type 1 diabetes is characterized by the rapid onset of severe hyperglycemia and ketoacidosis, with subsequent poor prognosis of diabetes complications. Causative mechanisms for accelerated β-cell failure are unclear.RESEARCH DESIGN AND METHODSSubjects comprised three autopsied patients who died from diabetic ketoacidosis within 2–5 days after onset of fulminant type 1 diabetes. We examined islet cell status, including the presence of enterovirus and chemokine/cytokine/major histocompatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
157
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(172 citation statements)
references
References 44 publications
12
157
3
Order By: Relevance
“…Cultured human islets have been shown to secrete CXCL10 following enterovirus infection [37]. In a recent report, Tanaka et al examined sections of pancreas from autopsy material derived from a deceased patient with fulminant type 1 diabetes, an acute subtype of type 1 diabetes identified in the Japanese population, and detected enterovirus capsid protein infiltration of CXCR3-bearing T cells and macrophages [38]. They also observed IFN-γ and CXCL10 in all subtypes of islets.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured human islets have been shown to secrete CXCL10 following enterovirus infection [37]. In a recent report, Tanaka et al examined sections of pancreas from autopsy material derived from a deceased patient with fulminant type 1 diabetes, an acute subtype of type 1 diabetes identified in the Japanese population, and detected enterovirus capsid protein infiltration of CXCR3-bearing T cells and macrophages [38]. They also observed IFN-γ and CXCL10 in all subtypes of islets.…”
Section: Discussionmentioning
confidence: 99%
“…Although immunohistochemical studies have suggested the expression of type I IFN (10,11) and some ISGs (12,13) in T1D islets, other studies have failed to detect type I IFN in pancreata from subjects with diabetes (14). End point PCR, with no or limited quantitative value, has suggested IFN-a expression to be more prevalent in T1D than in control pancreata (15,16), but this has not been confirmed by quantitative methods.…”
mentioning
confidence: 97%
“…Enterovirus infection of the pancreas induces the co-expression of IFN-c and CXCL10 (CXC chemokine ligand 10) in betacells along with MHC-II expression. Hyperexpression of MHC-I in some islet cells of the pancreas and subsequent activation followed by attraction of autoreactive T cells and macrophages to the islets have also been reported [137].…”
Section: Altered Mhc Response During Viral Infectionmentioning
confidence: 89%